Kondisi Sosial Ekonomi Rumah Tangga dan Masalah Stunting Balita di Indonesia - - Umar; Tri Haryanto (MediaTrend, 2019)
Stunting has become a global issue. Indonesia is the fifth country with the highest prevalence of stunted children. This study aims to analyze the effect of household socio-economic conditions on stunting in Indonesia. The study is using cross section data. Data resources are obtained from The Health Research and Health Development Agency by the 2010 Ministry of Health Data Center. Study’s metode is using the logistic regression analyze. The result shows household socio-economic, food consumption expenditure, mother’s education level, mother status, family size, breas milk, immunization, childbirth assistant, sanitation and enviromental health have affected the possibility of a simultaneous and partial stunting. The result of the study can be a reference to the government in preventing childhood stunting.